Vulnerability Evaluation for Student Enrollment at SMKS Pandawa Bali Global Abiansemal - Indrianto, Indrianto; Edwar, Edwar (Sebatik, 2024)
The development of information technology has led to the adoption of digital student enrollment systems by various educational institutions, including SMKS Pandawa Bali Global Abiansemal. The school employs the CodeIgniter 3 framework with standard configurations to enhance efficiency, transparency, and accessibility in the student admission process. However, this technological progress also introduces significant security risks, such as potential data breaches, system integrity disruptions, and damage to the school's reputation. This study aims to evaluate the security vulnerabilities of SMKS Pandawa Bali Global’s online registration system through risk analysis and penetration testing. The research methodology involves a literature review, identification of vulnerabilities, risk assessment, and formulation of recommendations. The findings reveal several critical vulnerabilities, including risks of SQL injection attacks, Cross-Site Scripting (XSS), and insecure session management. To address these issues, the study recommends implementing security measures such as deploying a Web Application Firewall (WAF), enabling multi-factor authentication, conducting regular security testing, and providing security training for staff. By adopting these measures, the school can enhance the security and stability of its enrollment system, ensuring a smoother, safer, and more reliable student registration process in the future.